Voltage‐Controlled On/Off Switching of Ferromagnetism in Manganite Supercapacitors. Issue 1 (13th November 2017) - Molinari, Alan; Hahn, Horst; Kruk, Robert
Abstract: The ever‐growing technological demand for more advanced microelectronic and spintronic devices keeps catalyzing the idea of controlling magnetism with an electric field. Although voltage‐driven on/off switching of magnetization is already established in some magnetoelectric (ME) systems, often the coupling between magnetic and electric order parameters lacks an adequate reversibility, energy efficiency, working temperature, or switching speed. Here, the ME performance of a manganite supercapacitor composed of a ferromagnetic, spin‐polarized ultrathin film of La0.74 Sr0.26 MnO3 (LSMO) electrically charged with an ionic liquid electrolyte is investigated. Fully reversible, rapid, on/off switching of ferromagnetism in LSMO is demonstrated in combination with a shift in Curie temperature of up to 26 K and a giant ME coupling coefficient of ≈226 Oe V −1 . The application of voltages of only ≈2 V results in ultralow energy consumptions of about 90 µJ cm −2 . This work provides a step forward toward low‐power, high‐endurance electrical switching of magnetism for the development of high‐performance ME spintronics. Abstract : Ferromagnetism of ultrathin films of LaSrMnO3 is reversibly switched on/off using an ionic liquid electrolyte as charging/discharging medium. It is demonstrated that solid/liquid magnetic supercapacitors allow for giant magnetoelectric effects in combination with high performance in terms of device endurance, switching speed, and energy consumption.